(untitled) (World Bulletin of Public Health, 2025)
This study evaluates the impact of key immunohistochemical (IHC) markers on treatment outcomes in atypical endometrial hyperplasia (AEH), a precancerous condition associated with a significantly increased risk of progression to endometrioid adenocarcinoma. As management strategies differ considerably—ranging from fertility-sparing hormonal therapy to radical surgical intervention—identifying reliable biological predictors of treatment response is critical for personalized therapeutic decision-making. A total of 50 women with histologically confirmed AEH were included. Among them, 20 patients (40%) underwent detailed IHC profiling for Ki-67, p53, Bcl-2, estrogen receptors (ER), and progesterone receptors (PR). Marker expression was evaluated semi-quantitatively according to ESGO/ESMO recommendations. Treatment strategies were individualized based on clinical characteristics, reproductive goals, and biological phenotype; hormonal therapy was offered to suitable candidates, while high-risk patients received surgical management.